IMPLEMENTASI METODE PEMBELAJARAN FUN LEARNING UNTUK MENINGKATKAN SEMANGAT BELAJAR SISWA KELAS 2 MADRAH IBTIDAIYAH AL ISLAM PRAMPELAN - Maslakhah Ulin Nuha; Laili Syarifah; Milna Wafirah; Dakusta Puspitasari (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
The use of enjoyable learning methods (fun learning) is highly necessary for lower-grade students to support their development and create optimal interaction. The Community Service Team implemented this program at MI Al Islam Prampelan as a creative effort to transform the learning atmosphere from monotonous to engaging, with the primary goal of boosting the enthusiasm and motivation of 2nd Grade students. The approach utilized was Asset Based Community Development (ABCD), which focuses on leveraging and developing the existing assets and potential within the educational institution. The service results demonstrated that the application of the innovative Fun Learning method successfully established an interactive and pleasant learning environment, and significantly increased students' learning enthusiasm and engagement.